A Preliminary Study of the Effects of Personality Traits on Workplace Deviance in the Voluntary Sector - Lima, Li-Chen; Teha, Choon-Jin; Chan-Yin-Fah, Benjamina (International Review of Management and Marketing, 2016)
The purpose of this study was to empirically investigate a set of personality traits in relation to workplace deviance among volunteers at one of the Malaysia’s Emergency Relief departments. A cross-sectional survey was conducted with self-reported questionnaire. The participants were 200 volunteers attached to six emergency relief centers in Peninsular Malaysia. Data were analyzed using SPSS version 19.0 software. Data analysis procedures; descriptive statistics, Pearson product-moment correlation and hierarchical multiple regression analysis were conducted. The findings confirmed the importance of taking personality traits into consideration during the process of recruitment of volunteers to minimize workplace deviance. This study contributes on the crucial role of volunteers’ personality traits that can be an imperative factor to minimize workplace deviance. Keywords: Personality, Volunteer, Deviance JEL Classifications: J23, L31